Signal-Noise Ratio Control Subsystem of Digital Equipment for Transmission of "Strela" Relay Protection Commands - I. I. Zabenkov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Continuous measurement function of relative noise and interference level in the information transmission channel is considered as an important one for controlling parameters of high-frequency signal. The present paper simulates an algorithm for measuring signal-noise ratio in the transmission channel of high-voltage lines which is used in the digital equipment for transmission of relay protection and emergency automation commands of "Strela" complex.